Nicaragua : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Nicaragua. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Nicaragua highlights that social unrest and its aftermath eroded confidence and caused large capital and bank deposits outflows that resulted in a prolonged output contraction. Banks cut lending, which exacerbated the downturn. Faced with sharply lower revenues and a severe tightening in available financing, including on account of sanctions, the government was forced to cut spending and adopt a procyclical tax package. The economy is projected to continue to contract in the near term as it adjusts to weaker confidence and lower external financing. The sharp contraction in credit will continue to depress investment, and the tight fiscal and external financing situation will continue to drag down medium-term growth. The key risks relate to further erosion in confidence and renewed deposit outflows. The imposition of additional sanctions by trading partners could also heighten economic stress. It is recommended to maintain a conservative fiscal stance in 2020 remains the key to maintain macroeconomic stability. Curbing expenditures on goods and services will allow increased spending on social programs, social safety nets, and public investment, which would lead to more equitable and sustainable growth.